PHYTOTOXICITY TEST OF KEROSENE-CONTAMINATED SOIL USING BARLEY - & et al., Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to determine a phytotoxicity experiment with kerosene as a model of a total petroleum hydrocarbon (TPHs) as Kerosene pollutant at different concentrations (1% and 6%) with aeration rate (0 and 1 L/min) and retention time (7, 14, 21, 28 and 42 days), was carried out in a subsurface flow system (SSF) on the Barley wetland. It was noted that greatest elimination 95.7% recorded at 1% kerosene levels and aeration rate 1L / min after a period of 42 days of exposure; whereas it was 47% in the control test without plants. Furthermore, the percent of elimination efficiencies of hydrocarbons from the soil was ranged between 34.155%-95.7% for all TPHs (Kerosene) concentrations at aeration rate (0 and 1 L/min). The Barley could efficiently encourage the degradation of complete total petroleum hydrocarbons depending to plant growth parameters when the kerosene level in water was up to 1%. A rhizobacetria attached with Barley roots played a major role in biodegradation of Kerosene in contaminated soil when the initial kerosene concentration was 1%. This study also revealed that Barley and rhizobacteria can reclaim hydrocarbon-polluted water in a subsurface flow system.